A process variation resilient spintronic true random number generator for highly reliable hardware security applications. (November 2022) - Morsali, Mehrdad; Moaiyeri, Mohammad Hossein; Rajaei, Ramin
Abstract: True random number generators (TRNGs) are critical in cryptography and security systems. This paper presents a reliable TRNG relying on the stochastic switching of the spin-transfer torque magnetic tunnel junction (STT-MTJ) in the sub-critical current regime. Using an XOR-based structure in our proposed design eliminates the need for succeeding post-processing units while ensuring a reliable generation of random numbers, even in the presence of major variations. Moreover, utilizing gate-all-around (GAA) carbon nanotube field-effect transistors (CNTFETs) and the efficient structure of the proposed design leads to a low-power and high-performance operation. Comprehensive transient simulations verify the functionality of the proposed TRNG in fabrication process corners. According to the simulation results, our proposed TRNG has, on average, 53% and 63% lower power consumption and energy per bit, respectively, and a 70% smaller area compared to its counterparts. A statistical randomness test provided by the U.S. National Institute of Standards and Technology (NIST) validates the randomness quality of the generated random bitstreams.